A Review of International Criminal Law on Human Rights Violations to The Rohingya Ethnicity - Tisna Amidjaja, Ryigen; Dasuki; Putra Zenno Januarsyah, Mas (Alauddin Law Development Journal, 2024)
The Rohingya ethnic minority faces discrimination as a result of the policies and actions of the Myanmar government. This discussion will centre on the delineation of violations and the manner in which international law evaluates human rights transgressions perpetrated against the Rohingya ethnic group in Myanmar. The research methodology employed in this study is a normative juridical approach, specifically utilising legal ideas and norms that are applicable in broader society. The legal materials utilised encompass elementary, secondary, and tertiary legal sources. The grave human rights atrocities that took place in Myanmar can be categorised as international crimes, specifically genocide and crimes against humanity. These violations satisfy the significant standards of mass murder, widespread prejudice against religious minorities, and intentional targeting of specific ethnicities and communities. The crimes mentioned are delineated in articles 6 and 7 of the Rome Statute, which are under the purview of the International Criminal Court (ICC).